HOW EDUCATIONAL GAME CAN IMPROVE THE PLAYER’S METACOGNITIVE SKILLS - Dedi Imaduddin Dzaky; Rudy Hartanto; Silmi Fauziati; Ralf Bierig (JIKO (Jurnal Informatika dan Komputer), 2024)
Gamification is a basic concept of game mechanics which apply into non-game environments. Games as joyful playing is widely used in daily life, including in education. Game was assembled by fundamental elements which regulate not only how it was played but also what is the final goal of their mechanics. When a game is operated; the player's cognitive, affective, and psychomotor aspects are involved. Involving three domains was integrated into an environment which stimulated the cognitive dimension. By using more complicated mechanics it will cultivate the metacognitive of players. This paper investigated how educational games can improve the player’s metacognitive skill. Investigating was done by theoretically analysing. The invention of this work is that educational games can improve a player's metacognitive which consist of several stages, namely goal setting and planning, selection and strategy selection, monitoring and evaluation, organization and self regulation, and attention. So, learning the effort of clearing stages of Cat Mario would encourage students to memorize knowledge and pattern of question so they could clear the question and learn new stuff through metacognitive skills that are obtained by their gaming experiences.